Enhancing Counterterrorism Cooperation Through Intelligence Collaborations in Indomalphi (2018-2023) - Andalus, Mutia Kartika Andalus; Muradi, Muradi; Djuyandi, Yusa (Jurnal Keamanan Nasional, 2023)
Terrorism issues are rapidly evolving in the Southeast Asian region, particularly for Indonesia, Malaysia, and the Philippines as countries directly impacted by terrorism issues due to the presence and growth of terrorist groups that conducted criminal activities in Sulu Sea and the spreading of foreign terrorist fighter (FTF). Two cooperation have made as a response of the issues, such as Intelex Cooperation and Trilateral Cooperation Arrangement. Sharing intelligence information becomes one of the main cooperation. However, there are obstacles in the implementation of cooperation, including distrust, unsynergetic cooperation, and differences in the paradigms of handling terrorism issues within Indomalphi. Furthermore, this article aims to analyze how the collaborative efforts by Intelligences Agencies strengthen intelligence cooperation within Indomalphi on terrorism issues from 2018 to 2023, as the cooperation start in 2018 until the present. This paper employs a qualitative method. Primary data is obtained through interviewing expertise in this field, and secondary data is obtained through literature review. Data triangulation is used to validate the data. Four elements of Regional Security Complex Theory such as Boundary, Anarchic Structure, Polarity, Social Construction is used to understand and analyzed the dynamics of intelligence cooperation in the context of enhancing counterterrorism cooperation in Indomalphi. The research findings indicate that collaborative effort has made effectively by intelligences agency across Indomalphi’s Countries to strengthen the counter-terrorism cooperation through information sharing and coordination with all actors involved. However, the needs to formed national security and defense counsel, expanding responsibilities and field of work beside terrorism, and fostering Confidence Building Measure (CBM) would be useful for Indomalphi cooperation in the futures.